#TITLE_ALTERNATIVE# - SAMODRA WICAKSANA (NIM:15111087) Tim Pembimbing : Dr. Ir. Vera Sadarviana, M.T. ; Dr. Irwa, NUNGHATTA
Monitoring of landslides using RTS and TLS instrument, as the application of geodetic methods, contribute to record geometric phenomenon on changes in land surface area of the landslide as representing the movement of soil. Landslide areas in Cililin, Kab. Bandung selected as the location for the research conducted avalanche studies using RTS and TLS. The aim of this study was to obtain the results of the monitoring point of the movement vector and 3D surface model change Cililin landslide area. The method used is data collection at several epoch. RTS measurement data is used to get the value of the movement vector monitoring points Cililin landslide area. Point cloud data from measurement results TLS are used in the registration, filtering, meshing, and overlay process to create a 3D model of the surface changes Cililin landslide area. From research conducted over the measurement range from June 2015 to October 2015, the movement of the majority of the RTS monitoring points leads to the southeast, except XYZ002 point that leads to the northeast. For the results of a 3D surface model of change can not represent the actual situation, due to constraints in data processing methods TLS is used for measurements in landslide areas with dense vegetation and heterogeneous.